Psalm 101: A supplication for the restoration of society in the late post-exilic age - Botha, Philippus J. (HTS teologiese studies, 2016)
This article investigates the form and purpose of Psalm 101 from two perspectives: As a unique composition from the late Persian or early Hellenistic period, and in terms of its function within the context of Book IV of the Psalter. It is suggested that it was designed by exponents of wisdom and Torah piety to serve as a ‘royal psalm’ at exactly this location in the Psalter. It was meant to offer support to faithful Yahwists by criticising the apostate Judean aristocracy of its time of origin and serve as a prayer with which Yahweh could be beseeched to establish his righteous rule by judging evildoers and thus vindicating the faithful.